2019
DOI: 10.1111/1750-3841.14605
|View full text |Cite
|
Sign up to set email alerts
|

Complex Coacervation Between Gelatin and Chia Mucilage as an Alternative of Encapsulating Agents

Abstract: Complex coacervation between gelatin type B (GE) and chia mucilage (ChM) was studied. GE‐ChM were mixed at mass ratios of 1:1, 2:1, 3:1, 4:1, and 1:2 in a pH range of 1.50 to 5.00, maintaining a total solid concentration of 0.2% (w/w), using turbidity and viscosity tests to obtain the highest yield of complex coacervates. To characterize the complex coacervates, morphology and Fourier‐transform infrared spectroscopy (FTIR) were determined. The optimum yield for complex coacervation was achieved with a GE‐ChM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Oil also had a slight positive effect while EO had a slight negative effect.The samples differed statistically significantly (p <0.05). The results correlate with those obtained by Hernandez-Nava et al [25], who used the complex coacervation between gelatin and gum Arabic and gelatin and chia mucilage (CM) to microencapsulate oregano EO. Depending on the spray drying parameters, the bulk density in their study was in the range for G:GA 0.157-0.202 and 0.234-0.282 for G:CM.…”
Section: 2bulk Density Tapped Density Carr Index (Ci) and Hausner Rat...supporting
confidence: 88%
See 2 more Smart Citations
“…Oil also had a slight positive effect while EO had a slight negative effect.The samples differed statistically significantly (p <0.05). The results correlate with those obtained by Hernandez-Nava et al [25], who used the complex coacervation between gelatin and gum Arabic and gelatin and chia mucilage (CM) to microencapsulate oregano EO. Depending on the spray drying parameters, the bulk density in their study was in the range for G:GA 0.157-0.202 and 0.234-0.282 for G:CM.…”
Section: 2bulk Density Tapped Density Carr Index (Ci) and Hausner Rat...supporting
confidence: 88%
“…The important factor affecting the complex coacervation process is the protein-polysaccharide mass ratiodifferent ratios affect the intensity of interaction and complexation, due to the charge balance between protein and polysaccharide [25,32,33]. Statistical analysis showed that the obtained results were influenced by the mixing ratio, the essential oil, the oil used, and the interactions between them.…”
Section: 1complex Coacervation Yield Solid Yield and Encapsulation Ef...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the possible natural products for the total or partial substitution of G derived from animals in soft capsules, biopolymers extracted from plants, such as mucilage, gum and starch, have become a very attractive alternative. For instance, Hernández-Nava recently attained the complex coacervation between type B gelatin (GE) and chia mucilage (ChM) as an alternative to encapsulating agents [5]. On the other hand, da Silva reported the formation of polyelectrolyte complexes (PECs) based on type-A gelatin and gum Arabic [6], finding that the optimal complexation pH is the key parameter to obtain reproducible microcapsules with targeted features, regardless of the origin of the gum.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin is a biopolymer made from the partially hydrolyzed collagen from animal skin, bones, tendons, and other connective tissues (Sarbon et al., 2013; Sow, Tan et al., 2019). Gelatin has good film‐forming, gelling, foaming, and emulsifying properties, thus it is often used in food, pharmaceutical, photographic, and cosmetic industries (Hernández‐Nava et al., 2019; Sarbon et al., 2013; Yu et al., 2019). Worldwide, about 85% of gelatin is manufactured from porcine skin, cattle hides, and bovine bones (Sow & Yang, 2015).…”
Section: Introductionmentioning
confidence: 99%